EVALUASI DALAM KEGIATAN PEMBELAJARAN : KLASIFIKASI MODEL DAN TEKNIKNYA - Wina Apriana; Saswitri Indra; Ainil Mardiah; Adriantoni (STKIP Subang, 2025)
This research aims to understand various educational evaluation models and learning evaluation techniques applied in the teaching and learning process. The method used is a library research with data sources from various literature related to evaluation in the field of education. The results of the study show that evaluation models such as CIPP, gap model, formative evaluation, and summative have an important role in assessing educational programs from various aspects, ranging from planning, implementation, to final results. In addition, learning evaluation techniques use various forms of tests, such as oral, written, and action tests, which are classified based on their evaluation objectives, such as speed tests, ability tests, learning outcome tests, and diagnostic tests. All of these evaluation models and techniques complement each other in improving the quality and effectiveness of learning. The development of appropriate evaluation models and techniques is very necessary so that the learning process runs according to the goals and is able to improve the quality of student learning outcomes in a sustainable manner. Keywords: educational evaluation, test techniques, assessment